(untitled) (Baghdad Science Journal, 2011)
Thick films of poly(vinyl chloride)(PVC)& PVC doped with Zn(etx)2 salt complex have been prepared by cast method with fixed thickness almost (120±5) Microns. Optical studies were carried out in the wavelengths region(200-900)nm based on absorption & transmition measurement. Optical parameters such as absorption coefficient(?) ,refraction index(n) and extinction coefficient(K) were observed to be effected by adding the dopant.Electrical parameters such as real(?)& imaginary(?) part of dielectric constant were also calculated part of dielectric constant were also calculated from the optical parameters using Maxwell equation.